Learning-Informed Agency among Women and Its Impact on Household Well-Being - Syarnubi; Septia Fahiroh; Diana J. Fox (Women, Education, and Social Welfare, 2026)
Household well-being is increasingly recognized as a multidimensional construct shaped not only by material resources but also by the capacity of household members to make informed and adaptive decisions. This study examines the impact of learning-informed agency among women on household well-being, conceptualizing agency as the ability to translate accumulated learning experiences into informed judgment and purposeful action. Using a quantitative cross-sectional design, data were collected from 312 adult women actively involved in household decision-making and analyzed using latent variable modeling techniques. The results indicate that learning-informed agency has a substantial and statistically significant positive effect on household well-being (β = 0.61, p < 0.001), explaining 37% of the variance in household well-being. Measurement model assessment confirmed satisfactory reliability and validity of the constructs. These findings demonstrate that women’s learning-informed agency is a central mechanism through which learning contributes to household stability, emotional security, and adaptive resilience. The study advances theoretical integration between learning, agency, and well-being, while offering policy-relevant insights for women-centered learning and family development interventions.